2009
DOI: 10.1002/hyp.7476
|View full text |Cite
|
Sign up to set email alerts
|

Spatial delineation of soil erosion vulnerability in the Lake Tana Basin, Ethiopia

Abstract: Abstract:The main objective of this study was to identify the most vulnerable areas to soil erosion in the Lake Tana Basin, Blue Nile, Ethiopia using the Soil and Water Assessment Tool (SWAT), a physically based distributed hydrological model, and a Geographic Information System based decision support system that uses multi-criteria evaluation (MCE). The SWAT model was used to estimate the sediment yield within each sub-basin and identify the most sediment contributing areas in the basin. Using the MCE analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
121
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(137 citation statements)
references
References 32 publications
6
121
0
5
Order By: Relevance
“…Erosion is a natural process that is enhanced by human activities. It causes the loss of agricultural productivity and a decline of water quality [2][3][4]. It is estimated that about 10 million ha of cropland is lost in the world due to soil erosion every year [5] and is often a common occurrence in the Mediterranean and China [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erosion is a natural process that is enhanced by human activities. It causes the loss of agricultural productivity and a decline of water quality [2][3][4]. It is estimated that about 10 million ha of cropland is lost in the world due to soil erosion every year [5] and is often a common occurrence in the Mediterranean and China [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The studies that have been carried out in the Lake Tana basin focused on modeling the sediment load, lake level fluctuation and water balance, and runoff volumes and identifying the erosion hot spot areas, analyzing runoff processes through conceptual hydrological modeling, and hydrological and suspended sediment modeling [3,16,[25][26][27]. Studies outside the Lake Tana basin found that infiltration furrows decreased direct runoff and sediment load but not sediment concentrations in the first three years of observation when gullies were present [23,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…SWAT is often employed to simulate the discharge 15 in the Ethiopian highlands (Setegn, 2008;Setegn et al, 2009;Easton et al, 2010;Betrie et al, 2011;Setegn et al, 2011;Yasir et al, 2014). Easton et al (2010) and White et al (2011) modified SWAT to include saturation excess runoff which is one of the major runoff mechanisms in the highlands.…”
mentioning
confidence: 99%
“…Watershed management requires accurate discharge and sediment predictions. SWAT is often employed to simulate the discharge in the Ethiopian highlands (Betrie et al, 2011;Easton et al, 2010;Setegn et al, , 2009Setegn et al, , 2010aSetegn et al, , 2010bSetegn et al, , 2011Yasir et al, 2014). Easton et al (2010) and White et al (2011) modified SWAT to include saturation excess runoff, which is the major runoff mechanism in the highlands.…”
Section: Introductionmentioning
confidence: 99%